Investigation of some injuries in freestyle and greco-roman style Turkish wrestlers - Fatih Karakaş; Yener Aksoy (Ozlem Book Center, 2023)
The study's main purpose is to determine the disability status of elite Turkish wrestlers in the young and senior categories according to Freestyle and Greko-Romen wrestling styles and to determine the precautions to be taken to prevent possible injuries in today's wrestling. Fifty-eight wrestlers in Freestyle and 72 wrestlers in Greco-Roman style were followed. Student t-tests- and "chi-square" tests were used for statistical analysis. It has been determined that there is a difference in the injury exposure of the wrestlers during active sports according to the wrestling style (Chiquare = 9.82, p<0.05). In the distribution of total number of injuries according to wrestling year, those injured 2 or 3 times increased significantly as the wrestling year increased (Chi-square 21.55, p<0.001). There are significant differences in the neck, back, shoulder and collarbone, rotator caf, other muscles, nose, finger, elbow, knee and below the knee, ankle, chest, and abdominal regions among the injured areas of the wrestlers according to the style (p<0.05 and p<0,001). The difference in the distribution of injury types in training and competitions according to wrestling style was not statistically significant (Chi-square =1.02, p=0.196). A significant difference was found in the participation of the wrestlers in the competitions according to the styles when they were injured (p<0.001). It has been determined that freestyle and Greco-Roman wrestlers have more injuries during training. As the number of wrestling years increases, so does the number of injuries. Greco-Roman wrestlers were injured more in the neck, back, abdomen and shoulder regions than freestyle wrestlers. Freestyle wrestlers suffered more injuries in the knee and ankle region.